1976
DOI: 10.1007/bf00041613
|View full text |Cite
|
Sign up to set email alerts
|

Breeding for resistance to coffee berry disease caused by Colletrotrichum coffeanumNoack (Sensu Hindorf) in Coffea arabica L. I. Methods of preselection for resistance

Abstract: INDEX WORDSCoffee arabica, arabica coffee, coffee berry disease, Colletotrichum coffeanum, resistance breeding. SUMMARYTwo methods of preselection for resistance to coffee berry disease, by artificial inoculation of young coffee seedlings, have been developed recently at the Coffee Research Station in Kenya. The efficiency of these methods has been investigated in a series of experiments by comparing the results of the preselection tests with mature plant resistance, as indicated by visual field scores and art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 14 publications
3
48
1
Order By: Relevance
“…Although van der Vossen et al (1976) found possible correlation between hypocotyls test and reaction of CBD on expanding berries was not the case in this study. Genotypes CVT10 (Ctr127 x (N39 x Rume Sudan selfed F 2 ) and CVT14 (Ctr086 x (N39 x Rume Sudan Selfed F 2 ) showed CBD resistance when green expanding berries were artificially inoculated, but the hypocotyls did succumb to the disease.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Although van der Vossen et al (1976) found possible correlation between hypocotyls test and reaction of CBD on expanding berries was not the case in this study. Genotypes CVT10 (Ctr127 x (N39 x Rume Sudan selfed F 2 ) and CVT14 (Ctr086 x (N39 x Rume Sudan Selfed F 2 ) showed CBD resistance when green expanding berries were artificially inoculated, but the hypocotyls did succumb to the disease.…”
Section: Discussioncontrasting
confidence: 66%
“…The experiment was arranged in the laboratory in a completely randomized design (CRD) with three replications. Hypocotyls at 5-6 weeks or 5-6 cm were sprayed and inoculated with suspension of C. kahawae strains at 2.0 x 10 6 conidia/ml twice at 48 hr intervals using the method by van der Vossen et al (1976). Three weeks after the date of first inoculation, coffee seedlings were individually scored for CBD symptoms which developed on the hypocotyls using a scale with a range of 0-4 which was developed by van der Graff (1982), where 0 is nil and 4 intense CBD infections.…”
Section: Experiments Under Controlled Conditionsmentioning
confidence: 99%
“…Many different coffee genotypes were tested with local C. kahawae isolates and differential pathogenicity was never observed in this country (van der Vossen et al, 1976). Moreover, differential interactions between host and pathogen population were seldom found in Ethiopia (van der Graaff, 1981).…”
Section: Fungal Variabilitymentioning
confidence: 99%
“…Many authors agree that the aggressiveness of the pathogen population shows variability between isolates from the same or different geographic origins (Firman and Waller, 1977;Omondi et al, 1997;Masaba and van der Vossen, 1978;van der Vossen, 1985;Manga et al, 1998;Manga, 1999;Varzea et al, 2002b, Varzea et al, 2001.…”
Section: Fungal Variabilitymentioning
confidence: 99%
“…The experiment was arranged in the laboratory in a completely randomized design (CRD) with three replications. Hypocotyls at 5 to 6 weeks old or 5 to 6 cm tall were sprayed and inoculated with suspension of C. kahawae strains at a concentration of 2.0 x 10 6 spores/ml twice at 48 hr intervals using a method described by van der Vossen et al (1976). The inoculum was prepared from 17-23 old days colonies of the four C. kahawae strains grown in 3.4% malt extract agar containing 0.04% streptomycin.…”
Section: Variation In Pathogenicity Of Colletotrichum Kahawae Isolatementioning
confidence: 99%